ANALISIS DAMPAK HALAL TERHADAP EKSPOR PRODUK MAKANAN DAN MINUMAN INDONESIA: PELUANG DAN TANTANGAN - Hafidz, Abdullah Al; Muharam Widiatmoko, Muhammad Rifman; Farizi, Ghibran Al (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This research analyzes the impact of halal policies on exports of Indonesian food and beverage products, with a focus on the opportunities and challenges faced. Indonesia, as the country with the largest Muslim population in the world, has great potential to become a major exporter of halal products on the global market. However, Indonesia's halal export contribution still lags behind other countries, such as Malaysia and Brazil. The main factors supporting halal exports include halal certification policies through Law no. 33 of 2014 as well as the increasing trend of consumption of halal products globally. However, there are several significant challenges, such as the low understanding of MSMEs about halal certification, limited logistics infrastructure, and intense competition from other countries. To overcome this challenge, the research recommends strategies in the form of halal certification training for MSMEs, optimizing digital platforms and e-commerce, as well as active promotion through international exhibitions. With this approach, Indonesia is expected to expand its halal market share, increase global competitiveness, and encourage economic growth through the national halal industrial sector.Keywords : Halal exports, halal policy, halal certification, MSMEs, global competitiveness, halal economy